Brain Functional Topology Alteration in Right Lateral Occipital Cortex Is Associated With Upper Extremity Motor Recovery - Huang, Qianqian; Lin, Dinghong; Huang, Shishi; Cao, Yungang; Jin, Yun; Wu, Bo; Fan, Linyu; Tu, Wenzhan; Huang, Lejian; Jiang, Songhe (Frontiers in Neurology, 2022)
Stroke is a chief cause of sudden brain damage that severely disrupts the whole-brain network. However, the potential mechanisms of motor recovery after stroke are uncertain and the prognosis of post-stroke upper extremity recovery is still a challenge. This study investigated the global and local topological properties of the brain functional connectome in patients with subacute ischemic stroke and their associations with clinical measurements. Fifty-seven patients, consisting of 29 left-sided and 28 right-sided stroke patients, and 32 age- and gender-matched healthy controls (HCs) were recruited to undergo a resting-state functional magnetic resonance imaging (rs-fMRI) study; patients were also clinically evaluated with the Upper Extremity Fugl-Meyer Assessment (FMA_UE). The assessment was repeated at 15 weeks to assess upper extremity functional recovery for the patient remaining in the study (12 left- 20 right-sided stroke patients). Global graph topological disruption indices of stroke patients were significant decreased compared to HCs but these indices were not significantly associated with FMA_UE. Additionally, stroke patients’ local brain network structure was altered, and the altered regions were dependent on stroke site. Significant associations between local degree and motor performance and its recovery were observed in right lateral occipital cortex (R LOC) in the right-sided stroke patients. Our findings suggested that brain functional topologies alterations in R LOC are promising as prognostic biomarkers for right-sided subacute stroke. This cortical area may be a potential target to be further validated for non-invasive brain stimulation treatment to improve post-stroke upper extremity recovery.